Design of Control Loop Pairing in a UCT Bioreactor System - Azwar Azwar; Hisbullah Hisbullah; Ahmad Irgi; Wari Julyadi; Adisalamun Adisalamun; Mukhlishien Mukhlishien; R. Nasrullah R. Nasrullah; Abubakar Abubakar; M.F. Zanil M.F. Zanil; J.M. Ali J.M. Ali (Jurnal Serambi Engineering, 2022)
Yoghurt is a pro-biotic beverage produced from the fermentation process of milk, namely from vegetable milk (soy milk) or animal milk (goat's milk and cow's milk). During the fermentation process, the chemical reactions that occur will turn milk into yogurt with the help of lactic acid bacteria. In the health sector, yogurt plays a role in increasing the body's immunity, digestive tract health and can prevent osteoporosis. In general, yogurt circulating in the community still has low nutritional content, so a more in-depth study needs to be done. The goal of this research is to examine the quality of yogurt by manipulating certain variables and adding other components to increase the yogurt's quality. Streptococcus thermophilus and Lactobacillus bulgaricus were used as starter as much as 12.5 mL each (10% of 500 mL of cream milk). The fixed variables in this study were the volume of goat's milk 500 ml, cream concentration 6%, pasteurization temperature 85°C, pasteurization time 15 minutes and fermentation temperature 45°C, while the independent variables were varying the length of the fermentation process for 3, 4, 5, 6, 7, 8 and 9 hours. From this study, it was concluded that yogurt with optimum results was obtained at a fermentation time of 6 hours, the pH value was 3.8, lactic acid content was 1.305%, protein content was 5.54%, fat content was 4.98%, and moisture content was 84.10%.